Alonso de castillo through morisco manuscript - zouhri, Walid (The Algerian Historical Journal, 2026)
This manuscript is an autograph or copy of a work, written by Alonso in the sixteenth century, contains standard and dialectal Arabic texts with translation into. the first chapter is texts from the walls of the Alhambra palace which are written by: ibn zamrak, Ibn alKhatib, and Ibn Jayyab. The uniqueness of this work lies in the fact that it is the oldest text that came to us from the narrations about the writings of the Al-Hamra Palace., the second chapter reads about the letters exchanged by Abu al-Abbas Ahmad al-Mansur al-Dhahabi The Sultan of Fez and Marrakech and others and a huge number of colloquial proverbs in the vernacular Andalusian tongue.